On Construction of Good Quaternary Additive Codes - Guo Luo-Bin; Liu Yang; Lu Liang-Dong; Li Rui-Hu (ITM Web of Conferences, 2017)
In this paper we present construction of some additive codes with very good parameters over the four elements finite field, each of these quaternary additive codes has double code words than its corresponding optimal linear code of the same length and minimum distance.